Preliminary Note on the Physical and Mechanical Properties of Fraxinius uhdei Grown at New forest, Dehra Dun, (U.P.) - Shukla, N. K.; sangal, S. k. (Indian Forester, 1980)
FraxinuS uhdei, a fast growing deciduous timber species native of Mexico, was introduced for the first time in 1960 in New Forest, Dehra Dun. With a view to examine the suitability of its timber for various industrial uses, some material from trial plantations was tested for the evaluation of its strength properties. The tests were carried out on 2 x 2 cm cross-section specimens on the material from 14 and 11 years old trees both in ’green’ and ’kiln dry’ conditions and the results are presented and discussed. The test results have also been compared with Fraxinus hookeri from Chamba (H.P.) and Tectona grandis from Malabar, Nilambur and Coimbatore. The results have indicated that Fraxinus uhdei is weaker in comparison to average Indian species. It has been suggested that Fraxinus uhdei should be tested more exhaustively from plantation trees of different age groups aod localities before suitable conclUsions could be drawn about its utilisation for specific industries uses.